COORDINATED HIGH-LATITUDE EXPERIMENTS FOR THE SIMULATION OF NUCLEAR-BURST EFFECTS ON VLF SYSTEMS. - Imhof, G. W.; Musser, J. M.; Oelbermann, E. J.; Volz, C., Jr; Banks, P. M. (1966)
This report describes some coordinated high latitude experiments which are being conducted for simulating nuclear-burst effects on long-range VLF propagation. The program consists of four parts: (1) Collection and study of VLF phase and amplitude data over four long range, high latitude VLF propagation paths. (2) Collection and study of ionospheric data (cosmic noise absorption data) near Reykjavik, Iceland. (3) Collection and study of other VLF data and ionospheric data from external sources (including satellite data). (4) Study and comparison of items 1 through 3 with nuclear test VLF data. (Author)